Assessing sitting and standing in college students using height-adjustable desks. - Chrisman, Matthew; Ye, Sangbeak; Reddy, Ashleigh; Purdy, William (Health Education Journal, 2020)
Objective: To examine if Arduino microcontrollers and Fitbits can serve as proxy measures for the direct observation of sitting and standing time in college students using height-adjustable standing desks. The preferred type of standing desks and reasons to use the desks were also assessed. Design: Classroom-based intervention, plus cross-sectional survey. Setting: Mid-sized Midwestern US university classroom. Method: Students were randomised to either a tabletop or stand-alone height-adjustable standing desk. They followed an alternating sit/stand protocol, then completed an 11-item questionnaire on preferences and reasons for or against using the desks. Data were collected in October 2018. Results: Twenty-two students completed the protocol (16 women; 15 in third or fourth year of study). Arduinos provided accurate representation of sitting. Correlations between Fitbits and Arduinos were moderate (.23–.49). Sixteen of the 22 participants preferred tabletop (vs stand-alone) height-adjustable desks. Main reasons to use standing desks were to improve health and preferring to stand. Main reasons for not using them were being tired and preferring to sit. Conclusion: Arduinos served as an adequate stand-in for direct observation, which has implications for studying the sedentary behaviours of large numbers of students simultaneously. More research is needed on using Fitbits for assessing sitting and standing time. Student preferences and reasons for/against using standing desks provide foundational evidence for standing desk interventions in this population.